String Processing and Information Retrieval 22nd International Symposium, SPIRE 2015, London, UK, September 1-4, 2015, Proceedings - Iliopoulos, Costas; Puglisi, Simon; Yilmaz, Emine (Theoretical Computer Science and General Issues, 2015)
This book constitutes the refereed proceedings of the 22nd International Symposium on String Processing and Information Retrieval, SPIRE 2015, held in London, UK, in September 2015. The 28 full and 6 short papers included in this volume were carefully reviewed and selected from 90 submissions. The papers cover research in all aspects of string processing, information retrieval, computational biology, pattern matching, semi-structured data, and related applications.